2023
DOI: 10.1038/s41467-023-36306-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ancestry and multi-trait genome-wide association meta-analyses inform clinical risk prediction for systemic lupus erythematosus

Abstract: Systemic lupus erythematosus is a heritable autoimmune disease that predominantly affects young women. To improve our understanding of genetic etiology, we conduct multi-ancestry and multi-trait meta-analysis of genome-wide association studies, encompassing 12 systemic lupus erythematosus cohorts from 3 different ancestries and 10 genetically correlated autoimmune diseases, and identify 16 novel loci. We also perform transcriptome-wide association studies, computational drug repurposing analysis, and cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 131 publications
(179 reference statements)
0
18
0
Order By: Relevance
“…Both mouse and human studies corroborate the role of T cells as central players in RA pathogenesis (2123). Similarly, for systemic lupus erythematosus (SLE), studies have identified an enrichment of B cell-specific putative regulatory elements and gene expression in SLE risk loci (19,20,24,25) consistent with the well-established role of B cells in SLE pathogenesis (26,27). Hence, there is precedence that the integration of GWAS with functional genomics datasets can identify cellular drivers in inflammatory diseases with complex pathogenesis.…”
Section: Introductionmentioning
confidence: 63%
“…Both mouse and human studies corroborate the role of T cells as central players in RA pathogenesis (2123). Similarly, for systemic lupus erythematosus (SLE), studies have identified an enrichment of B cell-specific putative regulatory elements and gene expression in SLE risk loci (19,20,24,25) consistent with the well-established role of B cells in SLE pathogenesis (26,27). Hence, there is precedence that the integration of GWAS with functional genomics datasets can identify cellular drivers in inflammatory diseases with complex pathogenesis.…”
Section: Introductionmentioning
confidence: 63%
“…When we performed the colocalization at increasing tertiles of the perturbation score within the NP-state (NP T1 -NP T3 ) and P-state (P T1 -P T3 ) ( METHODS ), we found that the eQTL signal for PXK colocalized in the lowest tertile of the NP cells (colocalization Pr NPT1 =53.1% Figure 5 f ). PXK encodes a sorting nexin (SNX) protein important for receptor internalization, organelle trafficking including endosomal trafficking 31 , and it has been previously implicated in the risk of SLE 32,33 . Our results shows that genetic regulation of PXK is particularly strong in lowly perturbed cell states.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the long non-coding RNA C5orf56 (5q31) has been identified for its protective role in IBD [ 97 ]. SCHIP1 (3q25) has been associated with SLE [ 98 ], while RNASET2 (6q27) has been identified as a risk gene for both vitiligo [ 99 ] and GD [ 100 ].…”
Section: Discussionmentioning
confidence: 99%